Utility of an Observational Social Skill Assessment as a Measure of Social Cognition in Autism. Issue 4 (9th October 2020) - Simmons, Grace Lee; Ioannou, Sara; Smith, Jessica V.; Corbett, Blythe A.; Lerner, Matthew D.; White, Susan W.
Abstract : Models of impaired social competence in autism spectrum disorder (ASD) highlight deficits in social cognition and social behavior. The Contextual Assessment of Social Skills (CASS) is a laboratory‐based assessment of conversation ability in which participants interact with trained confederates who act interested (CASS‐I) and bored (CASS‐B), sequentially. The increased ecological validity of the CASS allows for better generalization to real‐world social situations. Participants' perceptions of confederate behavior, assessed by the CASS Conversation Rating Scale (CRS), might offer additional utility as a metric of social cognition. The current study examined CASS confederate behavior (adherence to interested or bored condition) and both internal validity and convergent validity of the CASS as a measure of social behavior and social cognition. Fifty adolescents with ASD participated as part of a multisite randomized clinical trial. Adherence ratings were consistent across gender and site, with interested confederates significantly out‐performing bored confederates. The ability to distinguish between interested and bored confederates was positively associated with CASS social behavior and social cognition tasks, although social behavior during the CASS was not consistently associated with parent‐rated social behavior. Controlling for confederate behavior did not significantly alter these associations. Findings demonstrate strong internal validity of the CASS and, partially, external validity of the CASS as a measure of social cognition. Findings highlight nuanced differences in social behavior and social cognition. The CASS shows promise as an outcome measure for clinical interventions and should be incorporated into a multimethod battery to assess social competence in individuals with ASD. Lay summary: Social cognition and social behavior should be studied together to examine social competence in youth with autism. The Contextual Assessment of Social Skills (CASS), a behavioral observation measure, shows promise toward this end; findings suggest the CASS taps social cognition and social behavior when administered alongside a participant rating scale of their conversation partner's engagement. Continued research, including examination of the CASS, may inform best practices in comprehensive assessment of social competence in autism. Autism Res 2021, 14: 709–719 . © 2020 International Society for Autism Research and Wiley Periodicals LLC